Effect of Qualitative Exercises Using The (Vertimax) Device to Developing The Explosive Ability of Arms and Legs and the Skill of Long-Shooting for Youth In Handball - Ali Radhi Abdul Hussein; Nabeel Kadhim Hrebid; Jasim Jabber Mohamed (International Journal of Educational Review, 2022)
The importance of the research was to prepare qualitative exercises using the device (Vertimax) to develop the explosive ability of the arms and legs and the skill of long- shooting for young handball players. As well as knowing the effect of specific exercises using the device (Vertimax) to develop the explosive ability of the arms and legs and the skill of long-range shooting for young handball players. While the problem of the research was that there was a weakness in the explosive ability and the far shooting, so the player needs a high level of the explosive ability of the arms and legs in order to succeed the far shooting. Therefore, the researchers decided to develop specific exercises using the (Vertimax) device to develop the explosive ability of the arms and legs and the skill of long-range shooting for young handball players. As for the objectives of the research, it was to prepare qualitative exercises using the (Vertimax) device to develop the explosive ability of the arms and legs and the skill of long-range shooting for young players in handball. As well as knowing the effect of these specific exercises to develop the explosive ability of the arms and legs and the skill of long-range shooting for young handball players. As for the most important conclusions, it was represented that the specific exercises used on the device (Vertimax) have a positive effect on the development of the explosive power of the arms and legs and the skill of long-range shooting for young handball players. Therefore, the researchers recommend the need to use specific exercises using the (Vertimax) device to develop the explosive power of the arms and legs and the skill of long-range shooting for young players in handball.